2013
DOI: 10.1002/micr.22203
|View full text |Cite
|
Sign up to set email alerts
|

Internal mammary perforator vessels as recipient site for microsurgical breast reconstruction: A comparative histomorphometric analysis and incidence of degenerative vascular changes

Abstract: Although the IMP external diameters and lumen area were lower than the IM, the results of this study indicated that the tunica media layer in the IMP is less damaged than the other recipient vessels. The results of the comparative histological study permitted to describe additional advantages and disadvantages of using IMP as a recipient vessel for free flap breast reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…However, some studies have reported perforators arising from the first or fourth intercostal spaces in a few cases. 3,5,7 Although there is considerable variation in the use of IMAPs, clinical evidence supports a growing trend in the last decade, ranging from 9% in early studies to 83% in recent years. 2,4,6,8,17,18 The NOS uses a star system to assess the quality of a study, based on selection and outcomes; the quality of the study is rated as low (0-3 stars), medium (4-6 stars), or high (7-9 stars).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, some studies have reported perforators arising from the first or fourth intercostal spaces in a few cases. 3,5,7 Although there is considerable variation in the use of IMAPs, clinical evidence supports a growing trend in the last decade, ranging from 9% in early studies to 83% in recent years. 2,4,6,8,17,18 The NOS uses a star system to assess the quality of a study, based on selection and outcomes; the quality of the study is rated as low (0-3 stars), medium (4-6 stars), or high (7-9 stars).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported perforators arising from the first or fourth intercostal spaces in a few cases. 3 , 5 , 7 Although there is considerable variation in the use of IMAPs, clinical evidence supports a growing trend in the last decade, ranging from 9% in early studies to 83% in recent years. 2 , 4 , 6 , 8 , 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations